2018
DOI: 10.1146/annurev-arplant-042817-040314
|View full text |Cite
|
Sign up to set email alerts
|

Cell and Developmental Biology of Plant Mitogen-Activated Protein Kinases

Abstract: Plant mitogen-activated protein kinases (MAPKs) constitute a network of signaling cascades responsible for transducing extracellular stimuli and decoding them to dedicated cellular and developmental responses that shape the plant body. Over the last decade, we have accumulated information about how MAPK modules control the development of reproductive tissues and gametes and the embryogenic and postembryonic development of vegetative organs such as roots, root nodules, shoots, and leaves. Of key importance to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 165 publications
1
75
0
Order By: Relevance
“…We were interested in developing a biosensor for MAPK activity in Arabidopsis because of the central role that these kinases play in a wide range of signaling pathways. Our current understanding of MAPK function in Arabidopsis is based on extensive genetic and biochemical studies which have demonstrated roles for MAPK signaling in both stress responses and developmental regulation (Rodriguez et al ., ; Moustafa et al ., ; Xu and Zhang, ; Liu and He, ; Devendrakumar et al ., ; Komis et al ., ; Zhang et al ., ). Of the 20 MAPK genes present in the Arabidopsis genome, mutant phenotypes have been associated with mpk1 , mpk3 , mpk4 , mpk6 , mpk8 , mpk9 , mpk10 , mpk12 , mpk17 and mpk18 (Petersen et al ., ; Bush and Krysan, ; Wang et al ., , ; Hord et al ., ; Ren et al ., ; Jammes et al ., ; Walia et al ., ; Galletti et al ., ; Takahashi et al ., ; Zeng et al ., ; Stanko et al ., ; Enders et al ., ; Zhang et al ., ; Frick and Strader, ).…”
Section: Introductionmentioning
confidence: 99%
“…We were interested in developing a biosensor for MAPK activity in Arabidopsis because of the central role that these kinases play in a wide range of signaling pathways. Our current understanding of MAPK function in Arabidopsis is based on extensive genetic and biochemical studies which have demonstrated roles for MAPK signaling in both stress responses and developmental regulation (Rodriguez et al ., ; Moustafa et al ., ; Xu and Zhang, ; Liu and He, ; Devendrakumar et al ., ; Komis et al ., ; Zhang et al ., ). Of the 20 MAPK genes present in the Arabidopsis genome, mutant phenotypes have been associated with mpk1 , mpk3 , mpk4 , mpk6 , mpk8 , mpk9 , mpk10 , mpk12 , mpk17 and mpk18 (Petersen et al ., ; Bush and Krysan, ; Wang et al ., , ; Hord et al ., ; Ren et al ., ; Jammes et al ., ; Walia et al ., ; Galletti et al ., ; Takahashi et al ., ; Zeng et al ., ; Stanko et al ., ; Enders et al ., ; Zhang et al ., ; Frick and Strader, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that protein kinases can participate in most signal transduction in eukaryotic cells and control many cellular processes, including metabolism, transcription, cell cycle progression, apoptosis and differentiation, by adding phosphate groups to the substrate (phosphorylation) to alter the activity of the substrate, cellular localization or binding to other proteins. [78][79][80] Of significance, in this study, miR24-2 enhances Pim1 [92][93][94] and lysine methyltransferases SUV39H1 and Nanog regulate several oncogene expression in various cancer cells. 95,96 Recent work has provided a fact that the activation, regulation, and functions of MEKK kinases and tyrosine phosphorylation in several cancers.…”
Section: Discussionmentioning
confidence: 81%
“…HSP90s act as upstream and downstream modulators of YODA, while MPK6 and SPCH phosphorylation is controlled by heat stress. Genetic and pharmacological inhibition of HSP90s6 decreased the phosphorylation of MAPKs and enhanced stomatal density under normal conditions. On the other hand, induction of HSP90s by heat stress suppresses stomatal formation due to the over-phosphorylation of MAPKs and SPCH (Fig.…”
mentioning
confidence: 96%
“…YODA signaling pathway is essential to stomatal lineage specification 4,5,6 since it regulates the activities of transcription factors such as SPEECHLESS (SPCH) 7,8,9,10 . Heat-shock proteins 90 (HSP90s) are evolutionarily conserved molecular chaperones implicated in a broad range of signalling pathways being integrated in interaction networks with client proteins 11,12,13,14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation